PERANAN KEPALA SEKOLAH DALAM PENGEMBANGAN PROFESIONALISME GURU DI SMK NEGERI 2 TEMANGGUNG - Resya Fakhrunnisa; Ana Ratnasari (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2021)
The role of the principal in the development of teacher professionalism is an effort from the leadership of the principal to improve the quality of education. The purpose of this study was to describe the role of the principal as a leader in the development of teacher professionalism at SMK Negeri 2 Temanggung. This study uses qualitative research with a qualitative descriptive research strategy. This research includes ethnographic research that describes and interprets social and cultural groups. Data obtained from observations and interviews. Data collection techniques using observation, interviews and documentation. Data using descriptive analysis. The data validity used triangulation. The final results of the study concluded that the role of the principal as a leader in the development of teacher professionalism at SMK Negeri 2 Temanggung was carried out through supervision and motivating teachers to participate in teacher empowerment in MGMP training or education and training as well as improving facilities and infrastructure to support learning activities in order to improve quality of education.